Information Management and Information System Analysis to Support the Achievement of University Performance Agreements with the Government - Titis Sari Putri; Herman Tolle; Ismiarta Aknuranda (Faculty of Computer Science Universitas Indonesia, 2021)
State Universities in Indonesia have college performance agreement with Ministry of Education and Culture (MoEC) that consists of performance indicators and target achievements in a year. For assuring the integration, availability, and data validity of performance indicators, good information management with utilized information system is needed by entire working unit. Information management process to support data collection and target achievements on college performance agreement with MoEC in Brawijaya University still has many deficiencies. The process involves many stakeholders because it covers all areas of business in Brawijaya University (UB). Quality Asurance Center in UB as the unit that collects and processes the data of target achievements complained about data collection that takes a long time and it is often incomplete. The faculties, study programs, and other units experience the unavailability of most data and target performance indicators on information system that is used as reference for implementing business processes. The problem responded lightly by Information and Communication Technology Unit in Brawijaya University with consideration that Information System used is in accordance with the needs of the academic community. On the other hand, the responses about the problem from the lecturers, staff, and students are different. This research tries to explore and evaluate the problem and formulate the steps of transformations to refine the situation by using Soft Systems Methodology (SSM) with some additional Root Cause Analysis (RCA) stages. The major contribution of the research is giving the insights about the problem thoroughly comprising various perspective of stakeholders, transforming the refinement of the situation presented in conceptual model, and the stakeholders’ assessment of the conceptual model. This research also visualizes the implementation of RCA to dig up more perspective of the stakeholders and helps identifying the activities to construct conceptual model.